Recent advancements on biochars enrichment with ammonium and nitrates from wastewaters: A critical review on benefits for environment and agriculture. (1st March 2022) - Jellali, Salah; El-Bassi, Leila; Charabi, Yassine; Uaman, Muhammad; Khiari, Besma; Al-Wardy, Malik; Jeguirim, Mejdi
Abstract: During the last decade, biochars have been considered as attractive and eco-friendly materials with various applications including wastewater treatment, energy production and soil amendments. However, the important nitrogen losses during biochars production using the pyrolysis process have limited their potential use in agriculture as biofertilizer. Therefore, it seems necessary to enrich these biochars with nitrogen sources before their use in agricultural soils. This paper is the first comprehensive review on the assessment of biomass type and the biochars' properties effects on N recovery efficiency from aqueous solutions as well as its release and availability for plants when applying the N-enriched chars in soils. In particular, the N recovery efficiency by raw biochars versus the type of the raw feedstock is summarized. Then, correlations between the adsorption performance and the main physico-chemical properties are established. The main mechanisms involved during ammonium (NH4 –N) and nitrates (NO3 –N) recovery process are thoroughly discussed. A special attention is given to the assessment of the biochars physico-chemical modification impact on their N recovery capacities improvement. After that, the application of these N-enriched biochars in agriculture and their impacts on plants growth as well as methane and nitrous oxide greenhouse gas emissions reduction are also discussed. Finally, the main future development and challenges of biochars enrichment with N from wastewaters and their valorization as biofertilizers for plants growth and greenhouse gas (GHG) emissions reduction are provided. This systematic review is intended to promote the real application of biochars for nutrients recovery from wastewaters and their reuse as eco-friendly fertilizers. Graphical abstract: Image 1 Highlights: Biochars have low nitrogen contents which limit their use in agriculture. Biochars hybrid modifications allow high recovery yields of ammonium and nitrates. N-laden biochars promote the seedling stage and the vegetative growth. N-enriched biochars significantly reduce the N2 O and CH4 emissions. N-enriched biochars promote sustainability and circular economy concepts.